Switzerland - Zobel, Derek, 1983- (Minneapolis, MN : Bellwether Media, 2011)
"Developed by literacy experts for students in grades three through seven, this book introduces young readers to the geography and culture of Switzerland"--Provided by publisher.
Where is Switzerland? -- The land -- Lake Geneva -- Wildlife -- The people -- Daily life -- Going to school -- Working -- Playing -- Food -- Holidays -- A place of peace -- Fast facts.
Includes bibliographical references (p. 31) and index.
Keywords: Switzerland -- Juvenile literature; Switzerland